Students Responses in Learning Pronunciation through English Songs at Sixth Grade Student at SD Al-Araf: Penelitian - Nurul Della Salwa; Meristika Moetia (Jurnal Pustaka Cendekia Pendidikan, 2026)
English pronunciation remains one of the most challenging skills for young EFL learners, and engaging, low-anxiety media such as songs are often recommended to support its development at the elementary level. This study aims to examine sixth-grade students' responses to learning pronunciation through English songs at SD Al-Araf. A quantitative descriptive research design was employed, involving 20 sixth-grade students selected through purposive sampling; data were collected using a 16-item Likert-scale questionnaire covering four aspects, namely interest, motivation, confidence, and perceived improvement, and analyzed descriptively using means, standard deviations, and percentages. The results showed that students' total scores (sum of 16 Likert-scale items) ranged from 56 to 77, out of a theoretically possible range of 16–80, with a mean total score of 70.15 (SD = 5.46); 75% of respondents were classified into the "Strongly Agree" category and the remaining 25% into the "Agree" category, with no students showing neutral or negative responses. The overall grand mean across the 16 items reached 4.38, or 87.7% of the maximum score, falling into the "Very High" category, with interest and enjoyment obtaining the highest mean scores while confidence, particularly regarding shyness in pronouncing words aloud, obtained the lowest. This study concludes that students perceived English songs as a highly effective affective and motivational medium that fosters an enjoyable, low-anxiety learning atmosphere, although sustained and structured practice is still needed to strengthen students' individual confidence. Teachers are therefore encouraged to continue using English songs while incorporating corrective feedback and opportunities for individual practice to further optimize students' pronunciation development.